Synthesis and Characterization Nanomagnetite by Co-precipitation - Rahimah Rahimah; Ahmad Fadli; Yelmida Yelmida; Nurfajriani Nurfajriani; Zakwan Zakwan (Universitas Negeri Medan, 2019)
Magnetite (Fe3O4) nanoparticles becomes a new innovation that gets attention of biomedicine scientists. Magnetite can be applied to cancer treatment as a drug carrier because it’s good biocompatibility and very low toxicity. The aim of this study was to determine the effect of temperature and retention time on the magnetite particle characteristics prepared by co-precipitation method. The first, FeCl3 and FeCl2 with 2:1 mole ratio were reacted with 10% NH4OH at 40 - 80°C temperatures during 1 – 30 minutes in a beaker glass. Subsequently, the precipitate was separated using filter paper and it dried into air oven at 100°C. The characteristic of obtained magnetite powder were determined using XRD and SEM. From XRD pattern indicates that magnetite formed at all temperatures with crystallite diameter in the range of 7-13 nm. The SEM results indicate the agglomeration of the magnetite particles with size in the range of 1.37 to 1.72 μm. In the other hand, the higher of temperature and retention time will make the agglomeration of the particles become more uniform. The increasing of temperature and the retention time will increase the magnetite crystallinity level.